2016
DOI: 10.1007/s10552-016-0760-3
|View full text |Cite
|
Sign up to set email alerts
|

Is adherence to diet, physical activity, and body weight cancer prevention recommendations associated with colorectal cancer incidence in African American women?

Abstract: Purpose The purpose of this study was to evaluate whether adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) cancer prevention recommendations was associated with colorectal cancer incidence in the Black Women's Health Study (BWHS). Methods In this ongoing prospective cohort of African American women (analytic cohort N=49,103), 354 incident colorectal cancers were diagnosed between baseline (1995) and 2011. Adherence scores for seven WCRF/AICR recommendations (adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Corresponding results in women were 26% to 55% lower risk and 39% to 59% lower risk in men [39]**. Nomura et al and Makarem et al also calculated recommendation adherence scores in smaller cohort studies but found no association with colorectal cancer risk [40, 41]. None of the four studies examined risk by anatomic location of the cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding results in women were 26% to 55% lower risk and 39% to 59% lower risk in men [39]**. Nomura et al and Makarem et al also calculated recommendation adherence scores in smaller cohort studies but found no association with colorectal cancer risk [40, 41]. None of the four studies examined risk by anatomic location of the cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[10] In this study they created a three-level adherence score with low adherence women meeting <3 recommendations and high adherence women meeting >4 recommendations. Similar to Romaguera, the large low-adherence category of 0–2.5 recommendations likely limited the ability to detect associations between the high and low adherence and CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Meeting these recommendations has been associated with several outcomes, including lower total and site-specific cancer incidence [25] and all-cause and cancer mortality;[69] however, previous research into the association between meeting the WCRF/AICR and colorectal cancer (CRC) risk is limited,[2, 10] and has not examined whether observed associations differ by sex. Previous work has also not examined the associations between individual recommendations and CRC risk.…”
mentioning
confidence: 99%
“…Very few studies have examined these associations among Blacks. In studies conducted in the Black Women’s Health Study only 8.5% of women met at least 4 of the guidelines, and although no association was observed between increased adherence and colorectal cancer incidence [10], increasing adherence was also associated with reduced breast cancer incidence [7]. Another study reported that BMI mediated nearly 18% of the association between Black race and breast cancer mortality, though non-significant [34].…”
Section: Discussionmentioning
confidence: 99%